KEPEMIMPINAN DALAM ISLAM - Sukatin; Andri Astuti; Zahratul Afiyah; Septia Ningsih; Agus Pranata; Ridho Tawakkal Jannah (Department of Islamic Education Management, 2022)
This paper is made to find out leadership in Islam. This study uses a library research method by collecting various written sources and other reference sources to obtain specific conclusions. Leadership is a way to lead a group. Islamic leadership is leadership based on the Koran and as-Sunnah. In this study, it is explained that Islamic leadership has duties and obligations for Islamic leaders that need to be considered, it is also explained how the characteristics of Islamic leaders are, and what are the principles of Islamic leadership. Islamic leadership has an important role in knowing the aspects that need to be considered by leaders, especially for Islamic leaders and Islamic leaders who lead according to what Allah Subhanahu wa ta'ala and Rasulullah shalallahu alaihi wasallam ordered because of what is seen by humans, especially Muslims. affect the suitability of what is led by a leader.